Sintilimab induced ICIAM in the treatment of advanced HCC: A case report and analysis of research progress - Ji, Hongxiang; Wen, Zhijian; Liu, Bin; Chen, Hongbiao; Lin, Qian; Chen, Zhan (Frontiers in Immunology, 2022)
Immune checkpoint inhibitor-associated adverse reactions (irAEs) is a clinical treatment issue that requires additional attention when ICIs brings significant survival benefits to patients with advanced hepatocellular carcinoma (HCC). Among them, ICIs-associated myocarditis (ICIAM) is a kind of severe irAEs with high mortality rate(17-50%). Despite its low incidence (PD1/PD-L1 related:0.41-0.8%), ICIAM can significantly disturb the decision making of therapeutic schemes and even the survival outcomes of patients. ICIAM induced by sintilimab has not been reported in any complete clinical studies yet and understanding the clinical characteristics involved may inform better practices for the management. Here, we reported a case of patient(male, 78y, advanced HCC),who experienced ICIAM induced by Sintilimub within a short course (day 1 of the second cycle,21days/cycle) and found that adequate baseline examination before the implementation of therapeutic scheme, regular monitoring of myocardial enzymonram and cardiac imagings were measures for the early detection, while glucocorticoid pulse therapy is still the best choice with timely and sufficient application. if necessary, the combination of other immunosuppressants may lead to better results. New predictive markers or examination methods are still needed to facilitate the early detection.